The financing of education in Guyana: Issues & strategies: First draft February 1996 - Tsang, Mun C.; Inter-American Development Bank. Regional Operations Department 3. Social Programs Division 3 (Inter-American Development Bank, 1997)
This study is a review of the financing of the entire education sector in Guyana. It examines financing sources in education, patterns of expenditure on education, as well as the impact of expenditure on efficiency and equity in the education sector. The study is aimed at: 1) identifying opportunities for improving education efficiency and equity, 2) exploring options for mobilizing additional opportunities for education and cost savings, and 3) assessing the government’s capacity for meeting the counterpart requirements implied by investment in education from all sources.
Keywords: Educational finance